Multidisciplinary Approach to Hepatic Metastases of Intracranial Hemangiopericytoma: A Case Report and Review of the Literature - Dimitrios K. Manatakis; Spiridon G. Delis; Nikolaos Ptohis; Penelope Korkolopoulou; Christos Dervenis (Case Reports in Oncological Medicine)
Hemangiopericytoma is a rare primary tumor originating from Zimmerman’s pericytes, with significant metastatic potential. Hepatic metastatic disease requires an aggressive approach by a multidisciplinary team of dedicated oncology specialists, to prolong survival in selected patients. We report on a patient with recurrent hepatic metastases of grade II intracranial hemangiopericytoma 5 years after initial treatment, managed by a stepwise combination of liver resection, radiofrequency ablation, and transarterial embolization. Although metastatic disease implies hematogenous dissemination, long-term survival after liver resection has been reported and major hepatectomies are justified in patients with adequate local control. Liver resections combined with transarterial embolization are highly recommended, due to hypervascularity of the tumor.